Audiological evaluation in patients with Behçet's disease. Issue 8 (August 2014) - Sonbay, N D; Saka, C; Tatlican, S; Vuralkan, E; Aygener, N; Eren, C; Akin, I
Abstract Objective: This study aimed to determine the characteristics of hearing loss in patients with Behçet's disease. Methods: Twenty-six consecutive patients with Behçet's disease and a control group consisting of 25 age-matched healthy subjects were prospectively included in this study. Pure tone and speech audiometry, tympanometry, distortion product otoacoustic emission testing, and auditory brainstem-evoked response assessment were performed in the patients and controls. Results: The pure tone audiograms and the results of distortion product otoacoustic emission testing showed statistically significant hearing loss in the Behçet's disease patients (p < 0.05). Auditory brainstem-evoked response results were not significantly different between the patients and controls (p > 0.05). Conclusion: The findings of the present study demonstrated that audiological involvement is more frequent in patients with Behçet's disease than in healthy controls. Therefore, all patients with Behçet's disease should be regularly monitored by an otolaryngologist and be given information about the possibility of inner-ear involvement.